2020
DOI: 10.21203/rs.3.rs-34983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio for predicting clinical outcomes in COVID-19

Abstract: Background The epidemic of 2019 novel coronavirus (COVID-19) struck China in late December,2019, resulting in about 200000 deaths all over the world. Numerous observational studies have suggested that the neutrophil-to-lymphocyte ratio (NLR) and lymphocyte proportion and the platelet-to-lymphocyte ratio (PLR) are inflammatory markers. Our study aimed to detect the role of NLR, PLR in predicting the prognosis of COVID-19. Results Four hundred and fifteen consecutive patients were enrolled in Shanghai Public H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As shown in Table 1, most of studies were from China, and six studies were published from other countries [11,12,25,28,40,43]. Among of them, 41 studies with 10,335 patients were analyzed for the association of renal impairment with severity of COVID-19 [2][3][4]9,[11][12][13][14][16][17][18]20,21,23,[26][27][28][29][30][31][32][33][34][36][37][38][39][41][42][43][44][45][46][47][49][50][51][54][55][56][57]. In additions, 11 studies with 3759 patients reported the association of renal impairment with mortality of COVID-19 [1,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As shown in Table 1, most of studies were from China, and six studies were published from other countries [11,12,25,28,40,43]. Among of them, 41 studies with 10,335 patients were analyzed for the association of renal impairment with severity of COVID-19 [2][3][4]9,[11][12][13][14][16][17][18]20,21,23,[26][27][28][29][30][31][32][33][34][36][37][38][39][41][42][43][44][45][46][47][49][50][51][54][55][56][57]. In additions, 11 studies with 3759 patients reported the association of renal impairment with mortality of COVID-19 [1,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These results are supported by a study by 24 , in which there are significant differences in PLR in severe and non-severe COVID -19. Research by Zhang et al (2020) 34 also showed that there was a significant difference in PLR value for the severity of COVID -19. As an indicator of inflammation, PLR is primarily caused by megakaryocytes in the bone marrow recruiting neutrophils and other inflammatory cells to the site of injury.…”
Section: Resultsmentioning
confidence: 94%
“…The study from Yabing Guo and Wenhua Liang reported 2 sets of data. Therefore, 19 datasets were included in the quantitative synthesis (18 datasets from 16 studies combined with our case-control study) [6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Meta-analysesmentioning
confidence: 99%